EFFECT OF BED DISINFECTANTS AND SEASONAL INCIDENCE OF SILKWORM DISEASES IN STONE AND RCC REARING HOUSES - H. G. ANUSHA,; R. N. BHASKAR, (The Bioscan, 2015)
Silkworm diseases are the major problem in Sericulture, prevention of these diseases is one of the most important aspects in the success of commercial silkworm rearing. In order to obtain, high and stable cocoon yield it is necessary to decrease the pathogen load in the rearing environment. The most commonly used bed disinfectants by the farmers are viz., Active lime(4 kg), Vijetha(2-3 kg) and Ankush (3.5-4 kg). The variation was noticed with type of silkworm rearing house and cocoon yield. Further, in the medium stone house category (6 farmers) (40×20-50×30 ft) 5 to 15 per cent disease incidence was noticed during summer (5-15 and 5 -20 %) compared to rainy (10 % and 1%) in stone house and RCC house respectively. Furthercocoon yield of 85 and 95 kg/100 dfls was reportedwhen the famers applied 2kg Lime and 3 kg Vijetha respectively. The mean data from 4 farmers of medium RCC rearing house revealed that, a range of 0-1 %, 0-10 % and 5-20% disease incidence was recorded in rainy, winter and summer seasons respectively. On contrary cocoon yield of 95kg/100dfl was recorded in case sample number 4 eventhough the farmer did not applied any bed disinfectants.